Cashless Society – The Future of Money or a Utopia? - Nikola Fabris (Journal of Central Banking Theory and Practice, 2019)
In recent years we have witnessed a growing trend in cashless transactions as well as products and services sold exclusively in this way. Also, after the onset of the global financial crisis, private crypto currencies appeared that have raised some concerns. All of these changes beg the question of whether modern societies are moving towards a cashless society. This also raises a number of other dilemmas such as whether cashless societies have negative implications, whether they have what should be the response of economic policymakers, who would be potential winners and losers, and the like. The paper analyses the arguments both in favour and against cashless society, the future of crypto currencies, as well as potential responses of economic policymakers to the emergence of a cashless society. The paper concludes with the observation that it is not reasonable to expect the transition to a cashless society in the near future but the next step in the evolution of money might be the appearance of central bank digital currencies, at least in some countries.
Keywords: E40; E50; E52; 330; cashless society; crypto currencies; economic policy; central bank digital currencies.